Caracterização clínica e análise genética em pacientes com deficiência intelectual indeterminada, de uma instituição de internação crônica em Trindade-Goiás - Torres, Vinicius Montenegro (2019)
ID is a clinical manifestation that has heterogeneous and complex aetiology and 50% of it have no definite cause. In 48 patients institutionalized with Intellectual Disability (ID) and under 25 years of age, a detailed clinical, laboratory and radiological evaluation was performed. After this investigation, 27 individuals were classified as having undetermined ID and submitted to karyotype, MLPA of ID implicated subtelomeric regions, chromosomal microarray analysis and, when justified, PCR for screening of X Fragile Syndrome. In the clinical evaluation, these individuals with undetermined ID presented syndromic characteristics, family recurrence, severe intensity and association with short stature and weight. When greater severity of undetermined ID was observed, a greater frequency of male patients, low BMI, Epilepsy and Physical Deficiency was identified. Hearing Deficiency, Visual Impairment and short stature showed a tendency to exhibit the same behavior. Microcephaly and Autism Spectrum Disorder, contrary to previous studies, did not present this behavior. The karyotype and MLPA exams presented normal results in all cases. Clinical evaluation and molecular examination of relatives suggested that a patient had Spinocerebellar Ataxia Type 7. PCR screening for X Fragile Syndrome detected an affected individual. Twenty-three cases underwent chromosomal microarray analysis and seven pathogenic CNVs (30.43%) were detected. Microdeletions, microduplications and complex rearrangements were observed in different chromosomes and variable sizes. Rare genetic aberrations were detected and corroborated to define the phenotype associated with the subjects. Thus, obtained data indicated a strong genetic component in indeterminate ID. The current and previous studies corroborate to define chromosomal microarray analysis, the gold standard genetic test for initial evaluation in patients with undetermined ID. This technique is becoming more accessible and presents high sensitivity.